Displacement of Native FXYD Protein From Na+/K+-ATPase With Novel FXYD Peptide Derivatives: Effects on Doxorubicin Cytotoxicity - Liu, Chia-Chi; Kim, Yeon Jae; Teh, Rachel; Garcia, Alvaro; Hamilton, Elisha J.; Cornelius, Flemming; Baxter, Robert C.; Rasmussen, Helge H. (Frontiers in Oncology, 2022)
The seven mammalian FXYD proteins associate closely with α/β heterodimers of Na+/K+-ATPase. Most of them protect the β1 subunit against glutathionylation, an oxidative modification that destabilizes the heterodimer and inhibits Na+/K+-ATPase activity. A specific Cysteine (Cys) residue of FXYD proteins is critical for such protection. One of the FXYD proteins, FXYD3, confers treatment resistance when overexpressed in cancer cells. We developed two FXYD3 peptide derivatives. FXYD3-pep CKCK retained the Cys residue that can undergo glutathionylation and that is critical for protecting the β1 subunit against glutathionylation. FXYD3-pep SKSK had all Cys residues mutated to Serine (Ser). The chemotherapeutic doxorubicin induces oxidative stress, and suppression of FXYD3 with siRNA in pancreatic- and breast cancer cells that strongly express FXYD3 increased doxorubicin-induced cytotoxicity. Exposing cells to FXYD3-pep SKSK decreased co-immunoprecipitation of FXYD3 with the α1 Na+/K+-ATPase subunit. FXYD3-pep SKSK reproduced the increase in doxorubicin-induced cytotoxicity seen after FXYD3 siRNA transfection in pancreatic- and breast cancer cells that overexpressed FXYD3, while FXYD3-pep CKCK boosted the native protein’s protection against doxorubicin. Neither peptide affected doxorubicin’s cytotoxicity on cells with no or low FXYD3 expression. Fluorescently labeled FXYD3-pep SKSK was detected in a perinuclear distribution in the cells overexpressing FXYD3 and plasmalemmal Na+/K+-ATPase turnover could not be implicated in the increased sensitivity to doxorubicin that FXYD3-pep SKSK caused. FXYD peptide derivatives allow rapid elimination or amplification of native FXYD protein function. Here, their effects implicate the Cys residue that is critical for countering β1 subunit glutathionylation in the augmentation of cytotoxicity with siRNA-induced down-regulation of FXYD3.